A new approach to design S-box generation algorithm based on genetic algorithm. (23rd February 2021) - Çavuşoğlu, Ünal; Kökçam, Abdullah Hulusi
Substitution box (S-box) is one of the most important structures used for byte change operation in block encryption algorithms. An S-box structure with strong cryptological properties makes the encryption algorithm much more resistant to attacks. In this article, a powerful S-box generation algorithm design is presented using genetic algorithm (GA). In the GA-based S-box generation algorithm, the nonlinearity value which is one of the most important S-box evaluation criteria, has been processed. Quality of the generated S-boxes is determined by performance tests. Obtained performance results are compared with the S-boxes in the literature. It has been found that the presented algorithm generates S-boxes with strong cryptological properties.